Analisis Kebijakan Manajemen Transportasi Pemerintah Pada Pertumbuhan Ekonomi Pariwisata Jawa Timur - Ali Fathoni; Rohmatul Fitriyah Dewi; Muhammad Chusnul Khitam; Danu Kusbandono; Hery Suprapto (FKIP, Universitas Palangka Raya, 2022)
East Java Province has great tourism potential with tourism-based development that can provide economic growth for East Java Province. It is as an effort to maintain the existence of tourism development and government transportation policies through various tourist destinations and complete new infrastructure. With the rapid development of tourism, the tourism sub-sector makes a major contribution to local government revenues. So, the purpose of this study is to determine the results of the analysis of tourism policy and transportation policy. In the identification, it was found that the transportation variable plays a major role in tourism growth which also affects the economic growth of the surrounding community and the region so that the poverty rate decreases. The results of the study show that of the 13 selected variables have a significant influence on the value of supporting factors for tourism transportation policies, this reflects that among the variables proposed as the role of the government to facilitate the implementation of good tourism for tourism development and government policies, and the results turned out to have an effect on the management of tourist destinations in the implementation of tourism in East Java. Thus, the results of the median and std deviation are fully supported.